Orthography as an augmentative system in cerebral palsied - Shailashree C.N (Journal of All India Institute of Speech and Hearing, 1970)
Augmentative communication systems are found to facilitate communicative skills in most of the nonverbal individuals including cerebral palsied individuals.Though symbol systems such as pictorial drawings, rebuses, blissymbols and many others, may be used, traditional orthography as the symbol system maybe more appropriate in the present day situation in India - the reason being its acceptability, universality, generalisability, and utility in schools. However themajor drawback with traditional orthography is its opacity and idiosyncracy.